Children and youth speak for themselves - Johnson, Heather Beth, 1972- (Sociological studies of children and youth ;, 2010)
The theme of this volume is an outgrowth of one of the Section sponsored sessions at the 2006 ASA meetings in Montreal; "Children and Youth Speak for Themselves." The volume is a collection of articles from scholars who pay particular attention to children and/or adolescents' voices, interpretations, perspectives, and experiences within specific social and cultural contexts. Contributions include research stemming from a broad spectrum of methodological and theoretical orientations. This is a cutting-edge compilation of the most current child-centred scholarship on the sociology of children and childhood.